Gas production from dredged sediment. (15th February 2019) - Gebert, Julia; Knoblauch, Christian; Gröngröft, Alexander
Highlights: Landfilled dredged sediment monitored for gas production over 757 days. Gas potential varied between 2 and 12 m 3 MgDW −1, equalling 3–11% of OM degraded. Gas production related strongly to nitrogen which may serve as a good proxy. Share of degraded OM related inversely to ratio of organic carbon to nitrogen. OM mainly bound in heavy fraction >1.4 g cm −3, comprising the recalcitrant OM. GP757 outreached GP21 by the factor of four. Abstract: The anaerobic degradation of sediment organic matter leads to considerable gas production in constructions made from sediments and in landfills where contaminated sediments are disposed of, inducing problems with the mechanical stability of constructions or necessitating extraction and treatment of gas. However, little is known about the magnitude of gas generation from dredged sediment, hence validated input parameters for gas production modelling are missing. On the occasion of drillings performed for the installation of inclinometers on a mono-landfill for contaminated dredged sediment, eleven waste layers of known were sampled. Samples were analysed for gas generation in a long-term laboratory incubation experiment carried out for 757 days. It was found that the residual gas potential of the deposited dredged material ranged between 2 and 12 m 3 MgDW −1, relating to 3–11% of the organic matter being degraded. Correlation analyses with material properties suggest a strong role of nitrogen, either directly or as indicative parameter, with the gas potential increasing with total nitrogen content and the share of degradable carbon decreasing with increasing TOC/TN ratio. The by far greatest share of organic matter was bound in the heavy density fraction >1.4 g cm −3, suggesting that the readily available light organic matter pool had already been depleted during pre-treatment of the dredged sediment in dewatering fields and the subsequent years of landfilling. Consequently, the correlation of the remaining gas potential with heavy fraction nitrogen was even stronger than for bulk nitrogen. The gas potential as revealed from the long-term test correlated well with short-term values, but outreached the commonly applied potential measured for 21 days by the factor of four. The data improve the state of knowledge on gas production from the large mineral waste stream of dredged material and serve to improve gas production modelling for these types of wastes. The strong correlation of gas potential to TN suggests that TN may serve as a proxy to estimate total gas potential.